Vanlanddinghams celebrate golden wedding (Raton Range Raton, New Mexico, 1988)
Newspaper Article on the 50th Anniversary of Charles & Nadine Vanlandingham.
Master list item #: 42
File location is in the Raton File Cabinet
Keywords: Vanlandingham, Charles; Vanlandingham, Nadine; Clayton, Trevis; Clayton, Peggy; Vanlandingham, Glenda; Vanlandingham, Jerald; Vanlandingham, Edie; Vanlandingham, Rosa; McWilliams, Larry; McWilliams, Janet; Vanlandingham, Chuck; Vanlandingham, Hazel; Calvery Baptist Church; Wayland College; Betania Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Laramie, Wyoming; Lovington, Colorado; Texarkana, Texas; Fayetteville, Arkansas; Enochs, Texas; Plainview, Texas; Hart Camp, Texas; Cloudcroft, New Mexico